Pre-treatment with antiarrhythmic drugs for elective electrical cardioversion of atrial fibrillation: a systematic review and network meta-analysis . Issue 10 (3rd June 2022) - Um, Kevin J; McIntyre, William F; Mendoza, Pablo A; Ibrahim, Omar; Nguyen, Stephanie T; Lin, Sabrina H; Duceppe, Emmanuelle; Rochwerg, Bram; Healey, Jeff S; Koziarz, Alex; Lengyel, Alexandra P; Bhatnagar, Akash; et al.
Abstract: Aims: Our objective was to compare the efficacy of pre-treatment with different classes of anti-arrhythmic drugs (AADs) in patients with atrial fibrillation (AF) undergoing electrical cardioversion. Methods and results: We performed a systematic review and network meta-analysis (NMA) of randomized controlled trials (RCTs) comparing different AADs in patients with AF undergoing electrical cardioversion. We grouped AADs into five network nodes: no treatment or rate control, Class Ia, Class Ic, Class III, and amiodarone . Outcomes were (i) acute restoration and (ii) maintenance of sinus rhythm. We searched MEDLINE and EMBASE from inception until June 2020. We used Python 3.8.3 and R 3.6.2 for data analysis. We evaluated the overall certainty of evidence with the GRADE framework. We included 28 RCTs. Compared with no treatment or rate control, Class III AADs [odds ratio (OR): 2.41; 95% credible interval (CrI): 1.37 to 4.62, high certainty] and amiodarone (OR: 2.58; 95% CrI: 1.54 to 4.37, high certainty) improved restoration of sinus rhythm. Amiodarone improved long-term maintenance of sinus rhythm when compared with no treatment or rate control (OR: 5.37; 95% CrI: 4.00–7.39, high certainty), Class Ic (OR: 1.89; 95% CrI: 1.05–3.45, moderate certainty) and Class III AADs (OR: 2.19; 95% CrI: 1.39–3.26, high certainty). Conclusion: Before electrical cardioversion of AF, treatment with Class III AADs or amiodarone improves the acute restoration of sinus rhythm. Amiodarone is most likely to improve the maintenance of sinus rhythm after electrical cardioversion, but Class Ic and Class III AADs are also effective.